Pengimplementasian Manajemen Keuangan Terhadap Pencatatan Keuangan Usaha Toko Sembako di Kecamatan Rappocini Kota Makassar - Nurjannah Nurjannah; Andi Tenri Ampa (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
This research was carried out in order to find out how Financial Management is implemented in the financial records of grocery store owners, whether the Financial Management of each grocery store owner has recorded correctly in each of its financial records. The research method used is qualitative. The owners of Muliati Basic Food Shop and 88 Sembako were interviewed and observed during the research process. Descriptive analysis of data was used in this research. The findings of this study highlight the importance of financial record keeping in the grocery store industry as it allows basic food store owners to control operating costs, determine the business's profit and loss, and track its receivables.